UJI EFEKTIVITAS EKSTRAK SELADA AIR (NASTURTIUM OFFICINALE) SEBAGAI ANTIFUNGI TERHADAP PERTUMBUHAN JAMUR TRICHOPHYTON RUBRUM SECARA IN VITRO - Fashan Awlya Murfid Soetisnabrata (2020)
The tropical climate in Indonesia provides good support for the growth of fungi like T. rubrum. The challenge in treating fungal infections is the fungi that are resistant to existing antifungal drugs. Watercress (Nasturtium officinale) contains phenolic compounds, tannins, flavonoids, alkaloids, saponins, glycosides, steroids and triterpenoids which have antifungal. This study aims to determine the effectiveness of watercress extract in inhibiting the growth of T. rubrum. The antifungal activity test was carried out by the well diffusion method with the concentration of 20%; 40%; 60%; and 80%, ketoconazole positive control, and aquades negative control. The zone of inhibition was observed at 48 hours and 72 hours after giving watercress extract to the wells hole. The test used was One Way ANNOVA with a result of p = 0.000 which showed a significant difference in the effectiveness of watercress extract in inhibiting the growth of T. rubrum. Post Hoc test with Bonferroni showed p <0.05 in almost every treatment group, which means there was a significant difference. The measurement of inhibition zone showed the effectiveness of each extract concentration in inhibiting the growth of T. rubrum. Watercress extract with concentration 80% had moderate inhibitory and was the most effective in this study , Saponins have a high toxicity ability against fungi by denaturing proteins, so that intracellular fluids, metabolic substances, proteins and other nutrients come out until finally the fungi cells are damaged and die. Keywords: Antifungi, Watercress Extract, Trichophyton rubrum